High-spin Co3+ in cobalt oxyhydroxide for efficient water oxidation - Zhang, Xin (2024)
Cobalt oxyhydroxide (CoOOH) is a promising catalytic material for oxygen evolution reaction (OER). In the traditional CoOOH structure, Co3+ exhibits a low-spin state configuration ([Formula: see text]), with electron transfer occurring in face-to-face [Formula: see text] orbitals. In this work, we report the successful synthesis of high-spin state Co3+ CoOOH structure, by introducing coordinatively unsaturated Co atoms. As compared to the low-spin state CoOOH, electron transfer in the high-spin state CoOOH occurs in apex-to-apex [Formula: see text] orbitals, which exhibits faster electron transfer ability. As a result, the high-spin state CoOOH performs superior OER activity with an overpotential of 226 mV at 10 mA cm-2, which is 148 mV lower than that of the low-spin state CoOOH. This work emphasizes the effect of the spin state of Co3+ on OER activity of CoOOH based electrocatalysts for water splitting, and thus provides a new strategy for designing highly efficient electrocatalysts.